Implementation of a Novel Subspecialty Outpatient Palliative Medicine Head and Neck Cancer Clinic - Christine G. Gourin; Carole Fakhry; Nyall R. London; Leila J. Mady; Wayne M. Koch; Wojciech K. Mydlarz; David W. Eisele; Kaitlyn M. Frazier; Harry Quon; Aliyah Pabani; Brandi R. Page; Carmen Kut; et al. (The Laryngoscope, 2026)
ABSTRACT Objectives Head and neck cancer (HNC) patients have high palliative care (PC) needs. We reviewed our initial experience with a novel subspecialty HNC outpatient PC clinic, led by a Hospice and Palliative Medicine fellowship‐trained HNC surgeon. Methods We retrospectively reviewed 142 patients referred to a novel subspecialty HNC PC clinic between July 2023 and March 2025. Symptom evaluation included the revised Edmonton Symptom Assessment System (ESAS‐r), Patient Health Questionnaire‐9 (PHQ‐9) for Depression, Generalized Anxiety Disorder‐7 (GAD‐7), and frailty. Data were analyzed using cross‐tabulations, multivariable linear regression, and multivariable survival analysis. Results Most patients had incurable disease (73.9%), with significant improvement in ESAS‐r shortness of breath, ESAS‐r tiredness, GAD‐7, and PHQ‐9 scores at follow‐up. Mortality was 40.1%, and 84.2% of deaths occurred at home or in hospice. Aggressive end‐of‐life care occurred in 57.9% of patients and was associated with continued cancer‐directed treatment (79.4% vs. 26.1%), lower hospice use (55.9% vs. 82.6%), and death in an acute‐care facility (27.3% vs. 0%). Palliative immunotherapy was associated with reduced hospice duration (median = 15 days [IQR = 4–63]) compared to other cancer‐directed treatment (median = 27 days [23–63]) or supportive care (median = 68 days [26–162]). On multivariable analysis, surgery (HR = 0.08 [95% CI = 0.01–0.39]) and ≥ 3 PC visits (HR = 0.24 [0.08–0.73]) were independent prognostic indicators of survival. Conclusions Patients seen in a surgeon‐led subspecialty HNC PC clinic demonstrated observed longitudinal improvement in symptom scores, improved survival in patients receiving longitudinal PC, and a high rate of home or hospice deaths. These data suggest that subspecialist HNC PC adds value to multidisciplinary HNC care. Level of Evidence 4.